Towards a natural classification of the subtribe Philonthina (Coleoptera: Staphylinidae: Staphylinini): a phylogenetic analysis of the Neotropical genera. (20th February 2013) - CHANI‐POSSE, MARIANA
<x xml:space="preserve">Abstract</x> Philonthina, the largest subtribe of the rove beetle tribe Staphylinini, is a hyperdiverse group in the Neotropical Region, accounting for about half of the genera of the subtribe. Despite such diversity, Neotropical Philonthina have never been analysed phylogenetically, deterring formulation of a modern classification of the Staphylinini. A cladistic analysis of Neotropical Philonthina was performed based on 110 morphological characters and 77 terminal taxa. Representatives of Philonthina from other regions and other main lineages of Staphylinini, Arrowinini and Platyprosopini were included to test their relationships with Neotropical Philonthina. The major results are the monophyly of 11 of the 17 endemic Neotropical genera of Philonthina, the placement of Holisus Erichson (Hyptiomina) into this clade showing a sister group relationship to myrmecophile genera, and the position of Erichsonius Fauvel outside of Philonthina within Staphylinini. Six of the current seven species of Endeius Coiffait & Sáiz group with Neotropical species of Philonthus Stephens. The separation of Gondwana about 65 my and major landscape modifications in the vast interior of northern South America during the past 25 my is proposed to explain the evolution of the endemic Neotropical genera of Philonthina. The following taxonomic changes are proposed: Erichsonius Fauvel, 1874 now placed as incertae sedis in Staphylinini; Endeius Coiffait & Sáiz, 1968, n.syn. of Philonthus Stephens, 1929 and Endeius nitidipennis (Solier, 1849) placed as incertae sedis in Philonthina. The following new combinations are proposed: Philonthus franzi (Sáiz, 1971), comb.n., Philonthus loensis (Coiffait & Sáiz, 1968), comb.n., Philonthus lugubris (Sáiz, 1971), comb.n., Philonthus ovaliceps (Coiffait, 1981), comb.n., Philonthus punctipennis (Solier, 1849), comb.res. and Philonthus subpunctipennis (Coiffait & Sáiz, 1968), comb.n.Philonthus herberti, n.nov., is proposed for Philonthus franziSchillhammer, 1998, which is a junior secondary homonym of Philonthus franzi (Sáiz, 1971).